PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Widiya Sari; Hamdani Hamdani; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe research aimed. Analysis impression approaching contextual teaching and learning to mathematics result studying at 4th class elementary school 34 Pontianak City. Method  is was using is experimenal  method. The kind of research is was used is Quasi Experimental Design. Populatin of this research were student 4th class to 197 number sample of this research were student from 4th C to 33 numbers, as experiment class and student from 4th class D to 33 number as control class. Data collecting techniques is were used is measuring techniques. Based on analysis obtaining t count (2,580) > t table (1,670) which alternative hypotesis was accepted. As of can cencluded there were differences studying result between experiment class was using contextual teaching and learning impression and class was used deduktif impression. From calculated result effect siqe aqcuisiton ES as big as  0,46 with medium caractere. It mean studying by using contextual teaching and learning impression give medium effect to students 4th class result studying at elementary school 34 of Pontianak City. Keywords: Contextual Teaching and Learning Approaches,  Learning Outcomes,   Mathematics